(untitled) (Conferencea, 2023)
In this work, the physical properties of a composite polymer mixture of polypropylene (PP) with the addition of kaolin powder with a grain size (23 μm) were investigated. The polymer composite was prepared by mixing polymer blend (PP) with (5/10/15/20/25/30) wt.% kaolin powder to obtain the desired properties.